2016
DOI: 10.1186/s13054-016-1239-z
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of standard pupillometry practice in neurocritical care: an observational, double-blinded study

Abstract: BackgroundIn critical care units, pupil examination is an important clinical parameter for patient monitoring. Current practice is to use a penlight to observe the pupillary light reflex. The result seems to be a subjective measurement, with low precision and reproducibility. Several quantitative pupillometer devices are now available, although their use is primarily restricted to the research setting. To assess whether adoption of these technologies would benefit the clinic, we compared automated quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
142
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(152 citation statements)
references
References 28 publications
4
142
1
5
Order By: Relevance
“…8 Even more importantly, recent reviews identified a number of limitations of all prognostication studies, particularly the lack of blinding, which may have led to some degree of self-fulfilling prophecy and to an overestimation of the specificity of outcome prognosticators. [10][11][12] Preliminary studies in comatose CA patients found that quantitative PLR performed better than standard clinical evaluation in predicting outcome. [10][11][12] Preliminary studies in comatose CA patients found that quantitative PLR performed better than standard clinical evaluation in predicting outcome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 Even more importantly, recent reviews identified a number of limitations of all prognostication studies, particularly the lack of blinding, which may have led to some degree of self-fulfilling prophecy and to an overestimation of the specificity of outcome prognosticators. [10][11][12] Preliminary studies in comatose CA patients found that quantitative PLR performed better than standard clinical evaluation in predicting outcome. [10][11][12] Preliminary studies in comatose CA patients found that quantitative PLR performed better than standard clinical evaluation in predicting outcome.…”
mentioning
confidence: 99%
“…4,9 Automated infrared pupillometry provides a quantitative measure of pupil size, pupillary light reflex (PLR), and constriction velocity, and is emerging as a novel modality to evaluate brainstem function at the bedside in critically ill patients. [10][11][12] Preliminary studies in comatose CA patients found that quantitative PLR performed better than standard clinical evaluation in predicting outcome. [13][14][15] Here, we examined, using a blinded approach, the accuracy of quantitative PLR in predicting 1-year neurological recovery of comatose CA patients.…”
mentioning
confidence: 99%
“…This scenario might be very frequent in ICUs, notably because of the routine use of morphine derivatives, which promote the occurrence of miosis (15). Indeed, several reports indicate that opioids given at anesthetic doses likely result in a decreased pupillary light constriction below the threshold of 0.3 mm (12,16,17). Therefore, we cannot rule out the fact that some of areflexia were false positives in our study.…”
Section: Discussionmentioning
confidence: 82%
“…Therefore, we cannot rule out the fact that some of areflexia were false positives in our study. Some PAs could also have been missed because of inadequate examinations or monitoring intervals (12,13,17). To date, the best way to limit misdiagnosis of PAs is probably to objectively measure the size and reactivity of pupils by using a handheld automated pupillometer (11,12,15 17).…”
Section: Discussionmentioning
confidence: 99%
“…Given the development of pupilometers with an integrated automated pupil tracking system,10 PDR can be used during surgical procedures in the operation room for nociceptive state evaluation 11, 12, 13…”
Section: Introductionmentioning
confidence: 99%